PELAKSANAAN BIMBINGAN KELOMPOK DALAM MENINGKATKAN RASA PERCAYA DIRI PADA SISWA SMP SLB NEGERI KOTA PAREPARE - iis Susilawati; Darmawati Darmawati; Nur hikmah (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2016)
Guidance Group is a group of pedagogical in which there is an element of trust trust, cooperation, reciprocity between members in the group and the element of mutual help, while a group in which there are no elements above is a group of selfish, therefore, the activities of the implementation guidance the group itself to help distrust themselves on the individual. This study aims to determine how the implementation of group counseling in improving confidence in junior high school students SLB town of Pare Pare and how the results of the implementation of group counseling in improving confidence in junior high school students SLB town of Pare Pare. This research is descriptive qualitative case study approach and analysis techniques of observation, documentation, and interviews. The theory used in this research is the theory of Rational Emotive Therapy, and the theory of reality that explains the events, beliefs, and the consequences of junior high school students SLB town of Pare Pare. This study proves that the implementation of group counseling Schools State town of Pare Pare. Using the three components of the implementation of the guidance of the group are: implementation of group counseling skills, implementation guidance kelompokkesenian art of singing, and the third through the implementation of group counseling and information technology. The results of the implementation of group counseling conducted on students of SMP Negeri SLB town of Pare Pare students are more able to control emotions, self-acceptance, self-reliant and confident when socializing in the school environment and the community.